External debt stock, foreign direct investment and financial development: Evidence from African economies - Agyapong, Daniel (University of Economics Ho Chi Minh City, 2023)
Purpose The purpose of this paper is to examine the role external debt and foreign direct investment play in influencing financial development in Africa. Design/methodology/approach Annual data on external debt, foreign direct investment and financial development were extracted from the World Bank World Development Indicators from 2002 to 2015. The data employed were analysed within causal research design and the dynamic panel using generalized method of moment estimation approach. Findings The findings revealed that external debt and foreign direct investment have a significant positive relationship with financial development in African economies. Governments of the sampled economies should enact policies that would help attract high level of foreign direct investment as it contributes positively to financial development. Finally, governments of the sampled African economies should ensure foreign direct investment and external funds borrowed are channelled to productive sectors. Originality/value The paper analysed the relationship between external debt, FDI inflows and financial sector development. The paper is the first in terms of such analysis within the framework of the dual-gap framework, which is the first time in these kinds of studies. Previous studies have concentrated on the effect of financial sector on FDI and not the other way around.